PEWARISAN SASTRA LISAN SYAIR DI ERA DIGITAL: ANALISIS HAMBATAN DAN STRATEGI PELESTARIAN - Audia, Dianty Arifahmi; Berti, Berti (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to analyze the inheritance of Lampung oral poetry in the digital era, identify the obstacles faced, and formulate relevant preservation strategies. The study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, observation, and documentation. Research informants include traditional leaders, traditional poets, regional language teachers, and the younger generation. The results show that the transmission of Lampung poetry faces major obstacles in the form of declining interest among the younger generation, a lack of regeneration of traditional poets, limited documentation, and a lack of institutional support. Effective preservation strategies include integrating poetry into formal education, utilizing digital media for documentation and dissemination, and revitalizing poetry in traditional events, festivals, and community activities. Traditional leaders emphasize the importance of instilling local wisdom from an early age and the active involvement of the younger generation. This study concludes that a combination of traditional and digital approaches, as well as collaboration between schools, traditional communities, cultural leaders, and the government, is key to maintaining the sustainability of Lampung poetry as a living and relevant cultural identity in the modern era. Keywords: Oral Literature, Obstacles, Preservation Strategies